Oriented Films of Conjugated 2D Covalent Organic Frameworks as Photocathodes for Water Splitting - Sick, Torben; Hufnagel, Alexander G; Kampmann, Jonathan; Kondofersky, Ilina; Calik, Mona; Rotter, Julian M; Evans, Austin; Döblinger, Markus; Herbert, Simon; Peters, Kristina; Böhm, Daniel; Knochel, Paul; et al. (Journal of the American Chemical Society, 2018)
Light-driven water electrolysis at a semiconductor surface is a promising way to generate hydrogen from sustainable energy sources, but its efficiency is limited by the performance of available photoabsorbers. Here we report the first time investigation of covalent organic frameworks (COFs) as a new class of photoelectrodes. The presented 2D-COF structure is assembled from aromatic amine-functionalized tetraphenylethylene and thiophene-based dialdehyde building blocks to form conjugated polyimine sheets, which π-stack in the third dimension to create photoactive porous frameworks. Highly oriented COF films absorb light in the visible range to generate photoexcited electrons that diffuse to the surface and are transferred to the electrolyte, resulting in proton reduction and hydrogen evolution. The observed photoelectrochemical activity of the 2D-COF films and their photocorrosion stability in water pave the way for a novel class of photoabsorber materials with versatile optical and electronic properties that are tunable through the selection of appropriate building blocks and their three-dimensional stacking.